Atributos químicos e textura do solo em veredas conservadas e antropizadas no bioma Cerrado - SOUSA, Ricardo Fernandes de (2009)
The objective of this work was to study the soil of wetlands situated in conserved and altered environments (in agricultural and cattle areas), by determining the chemical attributes and texture of the soil. The study was carried through in the central region of Cerrado biome, in the state of Goiás, in wetlands situated in the City of Bela Vista de Goiás. There have been selected three wetlands for soil sampling: one conserved wetland, surrounded by natural vegetation (cerrado); one altered area, with occurrence of pasture in its adjacent areas; and another wetland, also altered, with the occurrence of agriculture in its adjacent areas. The samplings were taken in the months of April and May of 2008, through the use of lines of reference, according to their positions in the relief, in upper, average and lower position, following approximately the direction of the line of draining of the wetland. It has been collected samples in three depths: 0-10 cm; 10-20 cm and 20-40 cm. The variables studied have been: texture, pH in CaCl2 0.01 M; micronutrients (Cu, Fe, Mn, Zn and B), macronutrients (P, K, Ca, Mg and S), concentration of Al and potential acidity (H+Al), and soil organic matter content (SOM). It was verified that the clay percentages in the lower region of the relief are higher in altered environments and the percentage of silt are higher in the wetland adjacent to the agricultural area. In lower position of the relief, the concentrations of SOM are lesser in wetlands adjacent to the agricultural areas and pastures. In the conserved wetland the base saturation is higher in lower position of relief and, in this same position, the acidity (pH) and the aluminum concentration is lesser than that in the average and upper positions, occurring the inverse in farming landscapes.